(untitled) (The Pakistan Development Review, 1995)
Empirical evidence on the profitability of multinational enterprises vis-a-vis local finns in developing countries appears to be sparse and contradictory. This paper attempts to shed some light on this aspect through an analysis of the balance sheet data of a sample of manufacturing finns in Sri Lanka. The analysis does not support the generally-held view that multinational enterprises are more profitable than their local counterparts. It suggests that profitability cannot be explained by either origin (MNF/local finn) or sector, or age.